Anthropogenic CO2 accumulation and uptake rates in the Pacific Ocean based on changes in the 13C/12C of dissolved inorganic carbon. Issue 1 (13th January 2017) - Quay, P.; Sonnerup, R.; Munro, D.; Sweeney, C.
Abstract: The anthropogenic CO2 accumulation rate for the Pacific Ocean was estimated from the decrease in δ 13 C of the dissolved inorganic carbon measured on six World Ocean Circulation Experiment cruises during the 1990s and repeated during Climate Variability and Predictability in the 2000s. A mean depth‐integrated anthropogenic δ 13 C change of −83 ± 20‰ m decade −1 was estimated for the basin by using the multiple linear regression approach. The largest anthropogenic δ 13 C decreases occurred between 40°S and 60°S, whereas the smallest decreases occurred in the Southern Ocean and subpolar North Pacific. A mean anthropogenic CO2 accumulation rate of 0.41 ± 0.13 mol C m −2 yr −1 (0.82 ± 0.26 Pg C yr −1 ) was determined based on observed δ 13 C changes and is in agreement with previous observation‐ and model‐based estimates. The mean dissolved inorganic carbon DIC 13 inventory change of −178 ± 43‰ mol m −2 decade −1 was primarily the result of air‐sea CO2 exchange acting on the measured air‐sea δ 13 C disequilibrium of −1.2 ± 0.1‰. Regional differences between the DIC 13 inventory change and air‐sea 13 CO2 flux yielded net anthropogenic CO2 uptake rates (independent of ΔpCO2 ) that ranged from 0 to 1 mol m −2 yr −1 and basin‐wide mean of 1.2 ± 1.5 Pg C yr −1 . High rates of surface ocean DIC increase and δ 13 C decrease observed in the Drake Passage (53°S–60°S) support above average anthropogenic CO2 accumulation since 2005. Observed δ 13 C changes in the Pacific Ocean indicate that ocean transport significantly impacted the anthropogenic CO2 distribution and illustrate the utility of δ 13 C as a tracer to unravel the processes controlling the present and future accumulation of anthropogenic CO2 in the ocean. Key Points: Anthropogenic CO2 accumulation rate was estimated based on measured change in ocean δ 13 C between the 1990s and 2000s Net anthropogenic CO2 uptake rates independent of ΔpCO2 were estimated from measured δ 13 C changes Regional differences between anthropogenic DIC 13 accumulation and air‐sea 13 CO2 flux rates indicate importance of ocean transport